1992
DOI: 10.1111/j.1365-2710.1992.tb01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate digoxin monitoring

Abstract: The digoxin therapeutic drug monitoring service was evaluated during a 7-week period at Leeds General Infirmary. Data were collected for 88 patients who had one or more assays performed. The requesting clinician was contacted for each assay, and a questionnaire completed. Results were assessed to determine the appropriateness of the assay request and the action taken following receipt of the result. During the assessment period, 113 serum digoxin assays were requested. Data were collected for 88 (78%) of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…Rational use of therapeutic drug monitoring can help determine appropriate drug dosage and avoid toxic reactions. However, in previous studies the proportion of inappropriate monitoring ranged from 32 to 84% (Clague et al 1983;Copeland et al, 1992;Canas et al, 1999;Mordasini et al, 2002;Haim et al, 2002;Sidwell et al, 2003;Puche et al, 2004;Lippi et al, 2007;Orrico et al, 2011), suggesting that digoxin TDM is a tool that is difficult to use correctly. In these studies there was some variation in the criteria by which the quality of monitoring was assessed, making it difficult to directly compare findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rational use of therapeutic drug monitoring can help determine appropriate drug dosage and avoid toxic reactions. However, in previous studies the proportion of inappropriate monitoring ranged from 32 to 84% (Clague et al 1983;Copeland et al, 1992;Canas et al, 1999;Mordasini et al, 2002;Haim et al, 2002;Sidwell et al, 2003;Puche et al, 2004;Lippi et al, 2007;Orrico et al, 2011), suggesting that digoxin TDM is a tool that is difficult to use correctly. In these studies there was some variation in the criteria by which the quality of monitoring was assessed, making it difficult to directly compare findings.…”
Section: Discussionmentioning
confidence: 99%
“…Staff physicians are the Table 1. Appropriateness of digoxin level monitoring (Clague et al, 1983;Mordasini et al, 2002;Canas et al, 1999;Copeland et al, 1992 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies reported that digoxin TDM is frequently performed inappropriately that limits its benefits & increases unnecessary costs [7,9,10,11]. Therefore three criteria for proper use of digoxin TDM were suggested including proper indications, proper sampling time and proper interpretation of the measured digoxin level [12][13][14][15][16][17]. Several population pharmacokinetic of digoxin studies were reported that estimate the pharmacokinetic parameters of digoxin to be used in clinical practice for estimating appropriate dosage regimen [18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%